Supervising the Performance of Algerians Accountants and Audit ors to Minimize the Risk of Dive rgencc• in Measurements and Co mmunications of Accounting Information. - Lamare, Dr.Ahmed (Dirasat in Economics and Business, 2009)
Supervising the Performance of Algerians Accountants and Audit ors to Minimize the Risk of Dive rgencc· in Measurements and Co mmunications of Accounting Information. This essay is an attempt to show the great importance of accounting information quality ,in the economics units, which taken from the necessity to guide the accountants, and au ditors performance and to dir ect them and super vise their work, in a right way, in order to make such information of both, operational and account ting, a high quality, with mini mum, expected risk.